Seriously injured from multiple gunshot wounds - Mañana, Julio; Guicheff, Vladimir; Burstin, Jacobo (Cirugía del Uruguay, 2020)
The paper presents the results of the observation of a politraumatized patient in a serious condition due to multiple bullet wounds; this gave rise to problems in diagnosis, in the intensive preoperatory freatment, in surgical tactics and in a 'long and complicated postoperatory period during which time acute kidney insufficiency and respiratory insufficiency were. the cause of serious problems, fortunately satisfactorily solved. We believe this patient was saved thanks to the fact that the University Hospital is equipped with adequate means for dealing with this type of patient and has sufficient technical personnel.